2018
DOI: 10.1186/s12877-018-0753-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of aging, skeletal muscle mass, and tooth loss with masseter muscle thickness

Abstract: BackgroundPrevious studies have reported a relationship between masseter muscle thickness and tooth loss or limb muscle thickness. However, it is not yet known whether masseter muscle thickness is related to appendicular skeletal muscle mass, and grip strength. The purpose of this study was to determine which of the two variables—tooth loss or appendicular skeletal muscle mass index—is more strongly related to masseter muscle thickness, and to identify a suitable indicator of decreasing masseter muscle thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 28 publications
(35 reference statements)
6
52
0
2
Order By: Relevance
“…Elderly females with increased parathyroid hormonal levels and decreased estrogen levels could have a reduction in bone integrity over time 44,45 , and the associations among systemic osteoporosis, aging, and mandibular bone loss have been suggested [46][47][48][49] . Moreover, a generalized reduction in the total mass of the skeletal muscles and decreased size of the masticatory muscles in accordance with aging has been reported 50, 51 . The masticatory function also seemed to be related to masticatory muscle thickness and systemic muscle mass 52,53 .…”
Section: Discussionmentioning
confidence: 92%
“…Elderly females with increased parathyroid hormonal levels and decreased estrogen levels could have a reduction in bone integrity over time 44,45 , and the associations among systemic osteoporosis, aging, and mandibular bone loss have been suggested [46][47][48][49] . Moreover, a generalized reduction in the total mass of the skeletal muscles and decreased size of the masticatory muscles in accordance with aging has been reported 50, 51 . The masticatory function also seemed to be related to masticatory muscle thickness and systemic muscle mass 52,53 .…”
Section: Discussionmentioning
confidence: 92%
“…Several reports have indicated that the amount of protein consumed by the elderly is not sufficient (28)(29)(30)(31). Oral issues such as decreased appetite with age (32, 33), dysphagia (34), reduced muscle strength required for meat consumption (35,36), and periodontal disease (37) are noted as causes. In addition, aging of the digestive organs and gastric acid secretion decrease in the elderly (38), suggesting a decrease in digestive function to efficiently absorb the ingested protein.…”
Section: Discussionmentioning
confidence: 99%
“…However, some cranial muscles, including the jaw-closers, are very different in fiber-type composition than other skeletal muscle groups (i.e., limbs or abdomen). For instance, the masseter muscle, which originates from the zygomatic arch, contains both type I and type II fibers, but shows a predominance of type I muscle fibers, which are more strongly affected by inactivity rather than aging [126,127]. Given that the meal texture of older people frequently becomes softer, less power of tongue movement and of masseter muscle is required, which may result in decreased activity of these muscles.…”
Section: Sarcopenia and Oral Statusmentioning
confidence: 99%